1998
DOI: 10.1191/096120398678920299
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homovanillic acid and prolactin in systemic lupus erythematosus

Abstract: Prolactin (PRL) is an important immunoregulator and might have a role in the pathogenesis of systemic lupus erythematosus (SLE). The regulation of pituitary prolactin secretion is complex and involves a negative feedback process in the hypothalamus, in which dopamine plays the principal role. However, the main source of serum prolactin in lupus patients is still not clearly established. Since homovanillic acid (HVA), the principal metabolite of dopamine (DA), is removed from the brain into the blood, it would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…Estradiol stimulates prolactin secretion, and prolactin suppresses gonadal steroid synthesis (69,70). As shown in Table 4 and Figure 4, several studies have examined the relationship of prolactin and SLE in adults, comparing either the mean concentrations in patients with those of controls or normal and abnormal prolactin concentrations (hyperprolactinemia), with or without a control population (71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87). Seven of 10 female-only and 2 of 4 male-only SLE studies showed significantly increased serum prolactin concentrations in adult lupus patients compared with controls.…”
Section: Serum Prolactinmentioning
confidence: 99%
See 1 more Smart Citation
“…Estradiol stimulates prolactin secretion, and prolactin suppresses gonadal steroid synthesis (69,70). As shown in Table 4 and Figure 4, several studies have examined the relationship of prolactin and SLE in adults, comparing either the mean concentrations in patients with those of controls or normal and abnormal prolactin concentrations (hyperprolactinemia), with or without a control population (71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87). Seven of 10 female-only and 2 of 4 male-only SLE studies showed significantly increased serum prolactin concentrations in adult lupus patients compared with controls.…”
Section: Serum Prolactinmentioning
confidence: 99%
“…Other possibilities include cytokine-stimulated pituitary prolactin release (54,55), production of immunoreactive prolactin peripherally (98,99), or aberrant pituitary prolactin secretion in lupus patients (74,75). Some of these explanations are, however, superficially not compatible with the other steroid hormone abnormalities seen in female SLE patients.…”
Section: Serum Prolactinmentioning
confidence: 99%
“…Previous reports have demonstrated that plasma HVA levels in SLE patients are lower than those in healthy controls (Ferreira et al ., ). Another report showed that noradrenaline and dopamine plasma levels were increased in a patient with overlapping SLE and polymyositis syndromes (Nakajima et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Papers presented at the 5th International Conference on SLE suggested that changes in dopaminergic tone, 59 antibodies to prolactin, 60 or dysfunction of the hypothalamic-pituitary-glucocorticoid axis 61 occur in SLE. It should be noted, however, that one study presented in this issue showed that lupus patients with relatively inactive SLE may have normal hypothalamic-pituitary responses.…”
Section: Surveys Of Lupus Patients For Hyperprolactinemia Havementioning
confidence: 99%